12) If A = 2x – 3y +z, B = x + 7y - 6z and C = 3x – 2y + 9z then find
A+B - C.
Answers
Answered by
0
Answer:
6y-14z
Step-by-step explanation:
A + B-C
=2x – 3y +z + x + 7y - 6z-3x + 2y - 9z
=6y-14z
Answered by
0
Step-by-step explanation:
A+B = (2x-3y+z)+(x+7y-6z) = 3x+4y-5z
Now, A+B-C = (A+B)-C = (3x+4y-5z)-(3x-2y+9z)
A+B-C = 6y-14z
Hope you got the answer. Please mark my answer as brainliest.
Similar questions
Hindi,
2 months ago
English,
2 months ago
Environmental Sciences,
2 months ago
Science,
4 months ago
Math,
11 months ago